Pelatihan Literasi dan Numerasi Mahasantri Melalui Program Kepenulisan Karya Ilmiah - Anintyawati, Riska; Masithoh, Dewi (Universitas Negeri Gorontalo, 2024)
The importance of producing scientific papers in an academic environment is a necessity. However, it is a challenge for students who have just entered the world of writing. Therefore, this writing training activity aims to increase students' writing motivation and literacy and numeracy skills in compiling a scientific paper. The method of implementing activities uses the forum group discussion (FGD) method and the simulation method. The results of the activity showed that the writing training activities for students at Ma'had Aly Asslafiyyah went well. Participants have been able to prepare a draft of a scientific paper. Apart from that, 95% of participants had a strong desire to learn to improve their literacy and numeracy skills, as seen from the very positive response from participants participating in the training until the end of the activity. Through the Scientific Writing training activities at Ma'had Aly Assalafiyyah, students' enthusiasm and enthusiasm for improving their literacy and numeracy skills can be seen increasing, with follow-up plans aimed at strengthening the quality of learning and preparing students to contribute to the scientific world.